Energy levels and roughage sources for bulls on 140-day test - McKee, M.; Conway, K.L.; Fink, G.; Schalles, R.R.; Bolsen, K.K.; Zoellner, K.O. (Kansas State University. Agricultural Experiment Station, 2011)
Eight Hereford, 16 Angus, and 36 part Simmental bulls were tested for 140 days (October 15, 1974 to March 4, 1975) for weight gained. Bulls were divided into four groups and fed four rations that had been formulated for two energy levels (high or medium) and two sources of roughage (corn silage or oats and prairie hay). Average daily gains (lbs.) on the four rations were: high energy silage, 3.36; high energy oats and prairie hay, 3.31; low energy silage, 2.77; and low energy oats and prairie hay, 3.25.
1776-1976 "Buffalo to Beef" is known as Cattlemen’s Day, 1976
Keywords: Beef; Energy; Roughage; Average daily gains